Preliminary Study: Comparison of Antioxidant Activity of Cannabidiol (CBD) and α-Tocopherol Added to Refined Olive and Sunflower Oils - Matilde Tura; Mara Mandrioli; Tullia Gallina Toschi (Molecules, 2019)
This study evaluates the antioxidant activity of cannabidiol (CBD), added to model systems of refined olive (ROO) and sunflower (SO) oils, by measuring the peroxide value, oxidative stability index (OSI), electron spin resonance (ESR) forced oxidation, and DPPH• assays. Free acidity, a parameter of hydrolytic rancidity, was also examined. CBD was compared using the same analytical scheme with α-tocopherol. CBD, compared to α-tocopherol, showed a higher scavenging capacity, measured by DPPH• assay, but not better oxidative stability (OSI) of the oily systems considered. In particular, α-tocopherol (0.5%) showed an antioxidant activity only in SO, registered by an increase of more than 30% of the OSI (from 4.15 ± 0.07 to 6.28 ± 0.11 h). By ESR-forced oxidation assay, the concentration of free radicals (μM) in ROO decreased from 83.33 ± 4.56 to 11.23 ± 0.28 and in SO from 19.21 ± 1.39 to 6.90 ± 0.53 by adding 0.5% α-tocopherol. On the contrary, the addition of 0.5% CBD caused a worsening of the oxidative stability of ROO (from 23.58 ± 0.32 to 17.28 ± 0.18 h) and SO (from 4.93 ± 0.04 to 3.98 ± 0.04 h). Furthermore, 0.5% of CBD did not lower dramatically the concentration of free radicals (μM) as for α-tocopherol, which passed from 76.94 ± 9.04 to 72.25 ± 4.13 in ROO and from 17.91 ± 0.95 to 16.84 ± 0.25 in SO.